Gambaran Konsep Diri Orang dengan HIV AIDS (ODHA) di RSUD Kabupaten Indramayu - Virgiani, Bestina Nindy (Jurnal Keperawatan Profesional, 2019)
The self-concept of PLHIV is a decisive factor in interpersonal communication, because everyone behaves as much as possible according to his concept. The results of interviews with 10 PLWHA showed that the respondents still felt ashamed and felt that they were not useful for this life and felt excluded by their family and environment. The purpose of the study is to describe the concept of self (PLWHA). The design used in this study is quantitative with a descriptive approach. The sampling method uses accidental sampling as many as 188 respondents. The data collection tool uses a questionnaire. The results showed 113 respondents (60.1%) had a positive self-concept. 98 respondents (52.1%) had a positive body image, 116 respondents (61.7%) had an ideal positive self, 96 respondents (51.1%) had negative self-esteem, 167 respondents (83.5%) had an appearance negative role and 98 respondents (52.1%) had a positive self-identity. Conclusion in this study more than half the number of respondents have a positive self-concept, the respondent has accepted what happened to him and is ready to face life in the future and considers that life is a process of discovery. Keywords: PLWHA, self concept.